Disiplin Kerja dan Motivasi Terhadap Kinerja Karyawan - Sadat, Pamed Abdul; Handayani, Susi; Kurniawan, M. (INOVATOR, 2020)
This study aims to analyze the effect of work discipline and work motivation on employee performance. This research is quantitative descriptive. The population is the employees of PT. Perusahaan Gas Negara of the Palembang Branch Office. The sampling technique used is probability sampling. Data collection techniques used questionnaires and observations. Data analysis techniques are used for multiple linear regression, the coefficient of determination. The results showed that there was a simultaneous influence on the variables of work discipline and motivation on employee performance. Work discipline has a positive effect on employee performance. Motivation has a positive effect on employee performance.